Considerações sobre efeitos dinâmicos e carregamentos induzidos por fontes de excitação em estruturas industriais - Tania Maria Ribeiro Costa Assuncao (2009)
It is well known that the various sources of vibration existing in industrial environments which create the greatest day-to-day problems are due to machinery and equipment with moving rotating parts. Despite for the fact that these vibrations can be represented by a harmonic function, difficulties continue to be found in determining the magnitude of dynamic forces and in performing the analysis in a timely and precise manner.The purpose of this study was to address the issues and the most important considerations of a dynamic analysis of tall frame structures, in which are located equipment for industrial processes. For this, a study was done on the main causes of dynamic actions originated from the operation of industrial equipment and a case study was performed to analyze a steel-framed structure that supports a vibrating screen, whose main source of vibration is a rotating system with mass purposely nbalanced to cause the equipment characteristic movements. A visit to the equipment erection site was undertaken and the installation was studied, making possible the measurement of the magnitude of acceleration at various points of the actual structure. These measurements were performed with the use of an accelerometer while the vibrating screen was in operation. Computational models weredeveloped by the finite element method and, in one of the models, it had been represented the structure as realistically as possible, with the vibratory screen discretized. In the other models the vibrating screen was removed and its effects were represented with some variations and simplifications. Therefore, it was possible to compare the model acceleration results with the accelerations measured on site. This analysis demonstrated that the computational model which represents the equipment support springs, with the equipment mass and its dynamic force applied in the spring top, is the most appropriate to simulate the transmission of forces and the contribution of the vibrating mass to the responses of its support framing.